Cytosine base editors optimized for genome editing in potato protoplasts - Westberg, Ida; Carlsen, Frida Meijer; Johansen, Ida Elisabeth; Petersen, Bent Larsen (Frontiers in Genome Editing, 2023)
In this study, we generated and compared three cytidine base editors (CBEs) tailor-made for potato (Solanum tuberosum), which conferred up to 43% C-to-T conversion of all alleles in the protoplast pool. Earlier, gene edited potato (Solanum tuberosum) plants have been generated by poly ethylene glycol (PEG) mediated CRISPR/Cas9 transformation of protoplasts followed by explant regeneration. In one study, a 3-4 fold increase in editing efficiency was obtained by replacing the standard Arabidopsis thaliana AtU6-1 promotor with endogenous potato StU6 promotors driving expression of the gRNA. Here, we used this optimized construct (SpCas9/StU6-1::gRNA1, target gRNA sequence: GGTC4C5TTGGAGC12AAAAC17TGG) for generation of CBEs tailor made for potato and tested for C-to-T base editing in the Granular Bound Starch Synthase (GBSS) 1 gene in the cultivar Desiree. First, the Streptococcus pyogenes Cas9 was converted into a (D10A) nickase (nCas9). Next, one of three cytosine deaminases from either human hAPOBEC3A (A3A), rat (evo_rAPOBEC1) (rA1) or sea lamprey (evo_PmCDA1) (CDA1) was C-terminally fused to nCas9 and a uracil-DNA glycosylase inhibitor (UGI), with each module interspaced with flexible linkers.The CBEs were overall highly efficient with A3A having the best overall base editing activity with an averaged 34.5%, 34.5% and 27% C-to-T conversion at C4, C5 and C12, respectively, whereas CDA1 showed an averaged base editing activity of 34.5%, 34% and 14.25% C-to-T conversion at C4, C5 and C12, respectively. rA1 exhibited an average base editing activity of 18.75% and 19% at C4 and C5 and was the only base editor to show no C-to-T conversion at C12.